PERAN AKUNTAN PUBLIK DALAM PENGUNGKAPAN TINDAK PIDANA DI BIDANG KEUANGAN - WAHYUDI, RACHMAD (Dinamika Hukum, 2019)
The Public Accountant profession as a supporting profession in the disclosure of criminal acts in the financial sector is required to constantly improve competence and professionalism in order to meet the needs of service users (users) in carrying out public trust. The thing that needs to be mapped is the first to what extent a Public Accountant can play a role in disclosing criminal acts in the financial sector, second, in what scope of the role is carried out, third, how is the process to be effective and efficient. The research method is done with a sociological empirical juridical approach so that a clear and complete picture can be obtained about the ins and outs of the investigation carried out by a Public Accountant, the collected data is analyzed qualitatively and described exploratively. The results of the study found that the role of public accountants is very strategic as identified in 20 provisions at the level of the Act (Law), and can play a role in the scope of the private (private) financial sector and the state finance sector. Based on the primary data compilation, it is found that the investigation process can take place effectively and efficiently when using management norms and practices based on the preparation, planning, implementation and reporting of investigations. Keywords: Public Accountant, Investigation, Financial Crime